Pemberdayaan Masyarakat Dalam Pembangunan Desa - Hasiah, Rusdi Abadi Siregar & Syafri Gunawan & (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The problem in this research is how the implementation of Community Empowerment in Development in Sihoda-hoda Village, Padang Lawas Utara Regency has been implemented. Because the community empowerment that will be carried out has several obstacles so that it cannot be implemented properly. The purpose of this study is to describe and analyze community empowerment in development in Sihoda-hoda Village, Padang Lawas Utara Regency. The author raises the problem formulation, namely How to Empower the Community in Development and what are the supporting and inhibiting factors of community empowerment in development in Sihoda-hoda Village, Padang Lawas Utara Regency. The research method used in this research is a qualitative approach using descriptive methods, namely describing the phenomena or events that occur in the field. Data collection instruments used in this study consisted of interviews, observation, and documentation. The result of this research is that community empowerment in development in Sihoda-hoda Village has not been fully implemented by the Sihoda-hoda Village government. However, when viewed from the level of community participation in the planning stage it is quite high. Where the community participates in the formation of the village medium term development plan through village meetings (MUSDES) held by the village government of Sihoda-hoda. Supporting factors for the implementation of community empowerment in development in Sihoda-hoda Village are the existence of a Village Fund established by the North Padang Lawas Regency government, the willingness of the community to build and manage existing natural resources, and the existence of natural resources that are large enough to be managed by the government and society. While the inhibiting factors for the implementation of community empowerment in development in Sihoda-hoda Village are the lack of training to develop the potential of the Sihoda-hoda Village community, the lack of communication between the village government and the community, and vice versa, and the lack of community awareness of a sense of ownership with what they have.